Architecting the cloud : design decisions for cloud computing service models (SaaS, PaaS, and IaaS) - Kavis, Michael (Hoboken, New Jersey : John Wiley & Sons, Inc., 2014)
An expert guide to selecting the right cloud service model for your business Cloud computing is all the rage, allowing for the delivery of computing and storage capacity to a diverse community of end-recipients. However, before you can decide on a cloud model, you need to determine what the ideal cloud service model is for your business. Helping you cut through all the haze, Architecting the Cloud is vendor neutral and guides you in making one of the most critical technology decisions that you will face.
Chapter 11: SLA ManagementFactors That Impact SLAs; Defining SLAs; Managing Vendor SLAs; Summary; Chapter 12: Monitoring Strategies; Proactive vs. Reactive Monitoring; What Needs to Be Monitored?; Monitoring Strategies by Category; Monitoring by Cloud Service Level; Summary; Chapter 13: Disaster Recovery Planning; What Is the Cost of Downtime?; Disaster Recovery Strategies for IaaS; Recovering from a Disaster in the Primary Data Center; Disaster Recovery Strategies for PaaS; Disaster Recovery Strategies for SaaS; Disaster Recovery Hybrid Clouds; Summary.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Information technology -- Management; Cloud computing; Computer architecture; COMPUTERS -- Computer Literacy; COMPUTERS -- Computer Science; COMPUTERS -- Data Processing; COMPUTERS -- Hardware -- General; COMPUTERS -- Information Technology; COMPUTERS -- Machine Theory; COMPUTERS -- Reference; Cloud computing; Computer architecture; Information technology -- Management; Cloud computing; Computer architecture; Information technology -- Management; Electronic books; Electronic books